Zero Tolerance Policies in Education: Is it Time to Reconsider? - Sclafani, Chris (Advances in Social Sciences Research Journal, 2025)
Every school year, there is bound to be some sort of behavioral management challenge for school administrations across the United States. Some schools are standing by a policy of zero tolerance for the commission of certain acts. This is problematic for children because it stresses punishment over corrective measures, and it contributes to a culture of fear within the school community in its entirety. The time has come for school leadership to review and potentially revoke these harsh zero tolerance policies that have been shown to have very little overall positive impact upon the students or those serving them.